A Romance of the Republic - Child, Lydia Maria, 1802-1880 (Book collections on Project MUSE., 1997)
A Romance of the Republic, published in 1867, was Lydia Maria Child's fourth novel and the capstone of her remarkable literary career. Written shortly after the Civil War, it offered a progressive alternative to Uncle Tom's Cabin. Writer, magazine publisher and outspoken abolititionist, Child defied the norms of gender and class decorum in this novel by promoting interracial marriage as a way blacks and whites could come to view each other with sympathy and understanding. In constructing the tale of fair-skinned Rosa and Flora Royal -- daughters of a slaveowner whose mother was also the daug.